2022
DOI: 10.3390/min12101335
|View full text |Cite
|
Sign up to set email alerts
|

Study on Facies Modeling of Tight Sandstone Reservoir Using Multi-Point Geostatistics Method Based on 2D Training Image—Case Study of Longdong Area, Ordos Basin, China

Abstract: The Longdong area in the Ordos basin is a typical fluvial reservoir with strong heterogeneity. In order to clarify the distribution law of underground reservoirs in the Longdong area, it is necessary to establish and optimize a 3D geological model to characterize the heterogeneity of reservoirs. This is of great significance for accelerating the exploitation of tight sandstone gas in the southwest of the Ordos basin. This study takes the P2h8 member of the Ct3 research area in the Longdong area as an example, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Hussain, et al [21] identified reservoir rocks for lithofacies prediction by machine learning techniques. Zhang, et al [29] utilized a 2D training image of the multi-point geostatistics (MPG) method to model the facies of a tight sandstone reservoir. Liu, et al [30] analyzed influencing reservoir electrical parameters in a Quaternary mudstone reservoir containing biogas.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain, et al [21] identified reservoir rocks for lithofacies prediction by machine learning techniques. Zhang, et al [29] utilized a 2D training image of the multi-point geostatistics (MPG) method to model the facies of a tight sandstone reservoir. Liu, et al [30] analyzed influencing reservoir electrical parameters in a Quaternary mudstone reservoir containing biogas.…”
Section: Introductionmentioning
confidence: 99%
“…Although fractures are extensively developed in carbonate reservoirs, fracture attributes are highly variable [2]. As effective storage spaces and permeable channels for oil/gas in carbonate reservoirs, fractures are a central topic of reservoir research; understanding fracture patterns is of great significance to oil/gas exploration and development [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%